Chinese sectoral industrial policy shaping international trade and investment patterns - Evidence from the iron and steel industry - Peter Thomas in der Heiden (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2011)
In the three decades since China's economic opening to the world, the country's integration into the global economy has progressed by leaps and bounds. Especially after joining the WTO in 2001, international trade and investment flows have been on a steep upward trajectory. This process was not only driven by market forces but heavily influenced by government intervention in commodity and financial markets. While government authorities are strongly determined to promote closer economic integration with the rest of the world, they seek to supervise and control the process in order to carve out maximum benefits for domestic enterprises and the economy as a whole. Balancing market forces and industrial policy strategy, political decision makers have worked out an elaborate framework of measures to create an environment conducive to the development of several sectors deemed backbone or pillar industries. As one of them, the steel industry is subjected to numerous measures steering its development both in the home market and at the global market interface. By examining these mechanisms, this article aims to illustrate that sectoral industrial policy in China does not push for expanding exports and investments across the board but carefully and discretionarily promotes global integration in some areas while delaying it in others.
Keywords: 330; Economic integration; industrial policy; trade policy; trade restrictions; foreign direct investment; steel industry